The psychological impact on American healthcare workers during the COVID-19 pandemic: an initial scoping review - Sri Vaishnavi Konagalla; Maryam Azeem; Varsha Kumaravel; Vedasree Keerthi Machiraju; Mary Nguyen; Riley A. Decker; Sameera Pasham; Srija Doma; Ridhi Pendyala; Vinitha Shanmugam; Stephanie E. Waggel (Academia Mental Health & Well-Being)
The onset of the coronavirus disease 2019 (COVID-19) pandemic heavily distressed healthcare workers from around the world, with issues ranging from a lack of supplies and medication to panic surrounding public outbreaks. The consistent rise in infection and mortality rates, lack of specific medications and vaccines, extensive media coverage, massive workload, lack of personal protective equipment, and feelings of inadequate support all can contribute to the mental burden that healthcare staff endure. In these situations, healthcare workers are not only expected to work long hours but are also expected to work under overwhelming amounts of pressure. They are also at significant risk of being infected when treating ill patients. This review was designed to investigate the current literature on how the COVID-19 outbreak contributed to mental health symptoms among healthcare workers, specifically highlighting the importance of support from leadership and compared results between genders. The overall trends found specifically after the onset of the COVID-19 pandemic in the 21 studies reviewed included increased levels of psychological distress and depression in younger age groups and in women compared to men, increased burnout (which led to decreased resilience), decreased perceived hospital leadership support, and occupational differences, with nurses reporting higher rates of stress. This qualitative literature review aims to highlight the critical mental health challenges faced by healthcare workers during the COVID-19 pandemic and to identify effective strategies for providing support and interventions. These findings underscore the urgent need for comprehensive support systems and interventions to address the mental health challenges faced by healthcare professionals, thereby ensuring the sustainability and effectiveness of the healthcare system.